Daycare Center Attendance Buffers the Effects of Maternal Authoritarian Parenting Style on Physical Aggression in Children - Muñoz, José M.; Braza, Paloma; Carreras, Rosario; Braza, Francisco; Azurmendi, Aitziber; Pascual-Sagastizábal, Eider; Cardas, Jaione; Sánchez-Martín, José R. (Frontiers in Psychology, 2017)
A maternal authoritarian style has been related to the development of physical aggression during childhood and later future social problems; however, not too many studies have detected other than individual or family factors that may buffer this maternal effect. This work examines whether daycare center attendance may moderate the relationships between a mother authoritarian style and physical aggression. The study sample was 72 (40 girls) kindergarten children from Spain. Parents were asked to complete two questionnaires focused on individual family characteristics and parenting styles. At age 5, children physical aggression was assessed by direct observation at playtime; aggression scores at 6 was obtained by a peer-rated questionnaire. A least squared multiple regression was performed after controlling for children's level of physical aggression at 5, child sex and siblings. A positive contribution of maternal authoritarian style on physical aggression was detected. Daycare center attendance appears to attenuate the effect of the mother's authoritarian style on physical aggression, only in boys.